Abnormal small bowel motility in patients with hereditary transthyretin amyloidosis. Issue 9 (14th April 2018) - Wixner, J.; Törnblom, H.; Karling, P.; Anan, I.; Lindberg, G.
Abstract: Background: Gastrointestinal complications are common in hereditary transthyretin amyloid (ATTRm) amyloidosis. The underlying mechanisms have not been fully elucidated, and the patients' small bowel function remains largely unexplored. The aim of the present study was to compare the small bowel motility in ATTRm amyloidosis patients with that in non‐amyloidosis patient controls. Methods: ATTRm amyloidosis patients undergoing evaluation for liver transplantation were consecutively investigated with 24‐hour duodenojejunal manometry (n = 19). The somatostatin analogue octreotide was used to induce fasting motility. Patients with age at onset of ≥50 years were defined as late‐onset cases. For each patient, three age‐ and sex‐matched patient controls (n = 57) were selected from the total pool of investigated patients. Key Results: Manometry was judged as abnormal in 58% of the patients and in 26% of the patient controls ( P  = .01). Patients displayed significantly more daytime phase III migrating motor complexes than patient controls (median 4 vs 2, P  < .01), and had a higher frequency of low‐amplitude complexes (16% vs 4%; however, this difference did not reach statistical significance, P  = .10). Furthermore, late‐onset patients showed a delay in octreotide response (5.4 vs 3.8 minutes, P  < .01), but this was not observed for early‐onset patients or within the control group. Conclusions and Inferences: Patients with ATTRm amyloidosis displayed abnormalities in their small bowel motility more frequently than non‐amyloidosis patient controls, and the manometric pattern was probably best consistent with a combined neuromyopathic disorder. The delayed octreotide response in late‐onset patients warrants further investigation. Abstract : Gastrointestinal (GI) disturbances are common in hereditary transthyretin (ATTRm) amyloidosis and indirect measures have indicated an impaired small bowel motility. The present study shows that ATTRm amyloidosis patients display abnormalities in their small bowel motility more frequently than non‐amyloidosis patient controls. Late‐onset patients also show a delayed conversion to fasting motility after octreotide injection although they usually have less GI symptoms than early‐onset cases, which is a finding that warrants further investigation of potential differences in the enteric nervous system and gut endocrine cells between patients with early and late disease onset.